Strategi Meningkatkan Brand Awareness Mazda di Indonesia melalui Strategi Komunikasi Pemasaran - Dyva Clareta; Azadiel, Farell (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Mazda is a Japanese car manufacturer that has been in Indonesia for a long time. Mazda had changed APM (Brand Holder Agent) several times, however, since being under the direction of PT Eurokars Motor Indonesia, Mazda's development in Indonesia has been increasingly positive. The research method used is qualitative, with data collection through interviews, observation, and documentation. The research subject is Mazda, and the object of research is Mazda's marketing communication strategy in increasing brand awareness in Indonesia. Researchers concluded that there are four categorizations of Mazda marketing carried out in Indonesia to increase brand awareness, including building customer trust, promotion through digital marketing, marketing communication, and building brand awareness through Mazda's philosophy. However, Mazda also has obstacles in marketing its products due to the small number of dealers it has in Indonesia and the high selling price of products compared to other Japanese car brands. This is because Mazda is aiming for a more exclusive target market which makes dealers only exist in big cities. The high selling price of Mazda products is also proportional to what is obtained in the product and the quality of the materials used above other Japanese car brands. This study suggests that Mazda collaborate more with a more premium nature so that it is comparable to the image Mazda has built